Sign In
Ask Question
Mathematics
Goose
25 July, 23:20
Simplify: 36: (-3) + 2 (27:3 x - 2).
+3
Answers (
1
)
Rene Lawson
26 July, 00:14
0
-48
Step-by-step explanation:
36/-3 = - 12
-12 + 2 (27/3 * - 2)
27/3 = 9
-12 + 2 (9 * - 2)
9 * - 2 = - 18
-12 + 2 (-18)
2 * - 18 = - 36
-12 + - 36 = - 12 - 36
-48
Comment
Complaint
Link
Know the Answer?
Answer
Not Sure About the Answer?
Get an answer to your question ✅
“Simplify: 36: (-3) + 2 (27:3 x - 2). ...”
in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers
You Might be Interested in
What algebraic property is demonstrated in the equation below? 5 + 3 (2x - 7) = 5 + 6x - 21
Answers (1)
Is 3y=-2x+6 proportional or nonpropotional
Answers (1)
Using the addition or subtraction formulas for sine or cosine ... sinasinb = (cos (a-b) - cos (a+b)) / 2
Answers (1)
Find the product of x (4+3x+2)
Answers (1)
The circumference of a circle is divided into twelve equal arcs. The measure of each arc is degrees.
Answers (1)
New Questions in Mathematics
A+b=s+r for s I have no idea how to solve this
Answers (1)
What is the degree of a polynomial that has roots of - 2, 4i and - 4i?
Answers (1)
What is the x value in the solution to the system of linear equations 2x - y = 11 and x + 3y = - 5
Answers (1)
How do you find the tangent of a circle?
Answers (1)
Greatest common factor of 15 and 30 and 45
Answers (1)
Home
»
Mathematics
» Simplify: 36: (-3) + 2 (27:3 x - 2).
Sign In
Sign Up
Forgot Password?